The Implementation of Sister City Agreement on Tourism between the Special Region of Yogyakarta Indonesia and Kyoto Japan - Luna Tristofa; Aaron Tham (Universitas Muhammadiyah Yogyakarta, 2022)
Sister City between Yogyakarta and Kyoto is one of the most active cooperations in Indonesia. This cooperation covers various fields such as academics, economy, culture, and tourism. This paper focuses merely on the tourism sector program from 2015 to 2018 because Yogyakarta and Kyoto are famous tourism destinations. Moreover, from 2015 to 2018, there was a significant increase in Japanese tourists coming to Yogyakarta. It prompts an investigation on ‘how did the implementation of the cooperative agreement in tourism from 2015 to 2018 between the Special Region of Yogyakarta and Kyoto lead to mutual benefits?’. It is underpinned by two theoretical frameworks: the sister city concept and cultural diplomacy. This research aims to unpack the implementation of the Sister City Program between the Special Region of Yogyakarta and Kyoto in tourism from 2015 to 2018. This research revealed successful cooperation related to disaster risk and tourism management, promotion, and information.